2022
DOI: 10.1371/journal.pone.0264677
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification, and whole-genome sequencing of high-yield protease bacteria from Daqu of ZhangGong Laojiu

Abstract: A total of 296 strains of protease-producing bacteria were isolated and purified from medium-temperature Daqu produced by ZhangGong LaoJiu Wine Co. Ltd. After calculating the ratio of transparent ring diameter to colony diameter and measuring the protease activities, a strain of high-yield protease bacteria, called DW-7, was screened out with a protease activity of 99.54 U/mL. Through morphological observation, 16S rDNA sequence analysis, and physiological and biochemical tests, the isolated bacteria DW-7 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Few studies have identified the bacteria from the isolate, as biochemical tests and 16S rRNA gene sequences provide more reliable, accurate, and consistent bacterial identification (Y. Liu et al, 2022; Zhou et al, 2017). Following this, a complete genome of Bangladeshi isolates from diarrheal patient has been sequenced for the first time in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have identified the bacteria from the isolate, as biochemical tests and 16S rRNA gene sequences provide more reliable, accurate, and consistent bacterial identification (Y. Liu et al, 2022; Zhou et al, 2017). Following this, a complete genome of Bangladeshi isolates from diarrheal patient has been sequenced for the first time in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…The high-yielding cellulase Bacillus subtilis was screened from fermented grains, and this strain was screened from our previous work ( Liu et al, 2020 ). Fortified Daqu (experimental group FF Daqu) and traditional Daqu (control group CT Daqu) were produced from Daqu-making workshop of Henan Yangshao Distillery Co., Ltd., and the fortification of functional strains was based on the production process of traditional Daqu, which was carried out by uniform spraying of bacterial liquid onto the surface of the pressed and molded Daqu, with the concentration of bacterial liquid of 10 6 cells/mL (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Bacillus spp. was isolated according to the method described as previously, with minor modification ( Susanti et al, 2021 ; Liu et al, 2022 ). Heat the intestinal contents at 95°C for 5 min in order to separate out the Bacillus spores, followed by a 10-fold series dilution with sterile normal saline to ensure recovery of individual colonies on agar plates.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol was based on the previous method with minor modification ( Liu et al, 2022 ). Briefly, the selected strains were cultured at 37°C for 24 h and the inoculum was added at 10% (v/v) rate to the fermentation broth containing 20 g peanut meal and 20 ml distilled water in a flask.…”
Section: Methodsmentioning
confidence: 99%